Conjuntos controláveis por cadeias para ações de semigrupos em fibrados - Scanholato, Cintia Aparecida da Silva [UNESP] (2015)
The main objective of this work is to study the chain control sets for semigroups actions. The paper is organized as follows: First, in chapter 1, we presented some preliminaries necessary for the development of this work. Then, in chapter 2, we studied some topics of the Geometric Control Theory, such as, control sets, semigroup and system group, accessibility, controllability and approximate controllability for control sets. We also studied certain regions of phase space, called controllable system for control sets, where the control sets are approximately controllable. And, in the sequence, we studied the controllable sets by chains for control systems. Subsequently, in chapter 3, we studied the controllable sets for semigroups actions, also some of their properties, such as, two controllable sets for semigroup actions, are the same or are disjoint. We also saw the concept of transitivity set of a controllable set, and some properties, such as, is an open and dense set in which the semigroup acts transitively. After that, we studied the controllable sets by chains for semigroups actions in metric spaces, in which we show some results, for example, what characterizes ... (Complete abstract click electronic access below)